Analisis Pengaruh ROA dan DER terhadap Harga Saham pada Perusahaan Sektor Kesehatan yang Terdaftar di BEI Periode 2021–2025: Analysis of the Influence of ROA and DER on Stock Prices in Health Sector Companies Listed on the IDX for the 2021–2025 Period - Catherinne Febrianti Siahaan; Hazwa Falina Yusyafin; Nur Intan Rahmania; Raesa Sekar Nadya; Rizky Ramadhan (PT Cakrawarti Empat Proksi, 2026)
This study aims to analyze the effect of Return On Assets (ROA) and Debt to Equity Ratio (DER) on the stock prices of healthcare sector companies listed on the Indonesia Stock Exchange during the 2021–2025 period. This research uses a quantitative approach with secondary data obtained from annual financial statements and annual closing stock prices. The research sample consists of seven healthcare sector companies selected using purposive sampling based on specific criteria. The data analysis technique used is multiple linear regression with the assistance of IBM SPSS 23, after conducting classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results show that partially, ROA has no significant effect on stock prices, with a significance value of 0.416. DER also has no significant effect on stock prices, with a significance value of 0.340. Simultaneously, ROA and DER have no significant effect on stock prices, with an F value of 1.556 and a significance value of 0.226. The R Square value of 0.089 indicates that ROA and DER explain only 8.9% of the variation in stock prices, while the remaining percentage is influenced by other factors outside this study.